2007
DOI: 10.1175/mwr3288.1
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Analysis of Supercell Rear-Flank Downdrafts from Project ANSWERS

Abstract: Data collected during Project Analysis of the Near-Surface Wind and Environment along the Rear-flank of Supercells (ANSWERS) provided an opportunity to test recently published associations between rear-flank downdraft (RFD) thermodynamic characteristics and supercell tornadic activity on a set of 10 events from the northern plains. On average, RFDs associated with tornadic supercells had surface equivalent potential temperature and virtual potential temperature values only slightly lower than storm inflow valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
67
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(82 citation statements)
references
References 11 publications
9
67
0
1
Order By: Relevance
“…The associative relationship between cold pool buoyancy and tornadogenesis (Markowski et al 2002;Markowski 2002;Grzych et al 2007;Hirth et al 2008;Lee et al 2012) may be attributable to the resistance of negatively buoyant air within the cold pool to vertical acceleration (Markowski and Richardson 2014). Thus, an RFO warmed through advection/mixing of inflow air in a penetrating wake circulation could substantially reduce the stability of the RFO air near the surface circulation.…”
Section: Chapter 4 Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The associative relationship between cold pool buoyancy and tornadogenesis (Markowski et al 2002;Markowski 2002;Grzych et al 2007;Hirth et al 2008;Lee et al 2012) may be attributable to the resistance of negatively buoyant air within the cold pool to vertical acceleration (Markowski and Richardson 2014). Thus, an RFO warmed through advection/mixing of inflow air in a penetrating wake circulation could substantially reduce the stability of the RFO air near the surface circulation.…”
Section: Chapter 4 Discussionmentioning
confidence: 99%
“…Via analyses of Doppler radar and in situ surface observations collected during the Verification of the Origins of Rotation in Tornadoes Experiment (VORTEX), it was hypothesized that RFDs characterized by higher thermal buoyancy were more likely to support tornadogenesis, due to a higher potential for air in the RFD to accelerate upward and increase vertical vorticity via stretching (Markowski et al 2002;Markowski 2002;Grzych et al 2007;Hirth et al 2008;Lee et al 2012). However, it is also likely that the RFD realigns and distributes vorticity that is generated baroclinically within the RFD (Davies-Jones and Brooks 1993), suggesting that tornadogenesis may also be less likely to occur in the absence of a horizontal buoyancy gradient (i.e., having outflow that is too warm for baroclinic vorticity generation).…”
Section: Introductionmentioning
confidence: 99%
“…The vertically integrated buoyancy within the cold pool matters much more than the buoyancy next to the surface (Rotunno et al 1988). In supercell thunderstorms, tornado formation is sensitive to the negative buoyancy and equivalent potential temperature of the rain-cooled, vorticity-rich air that emanates from downdrafts (e.g., Davies-Jones 2015), with tornadogenesis likelihood generally increasing as buoyancy and equivalent potential temperature increase within the rain-cooled, vorticity-rich air-at least near the surface (e.g., Markowski et al 2002;Grzych et al 2007;Hirth et al 2008;Snook and Xue 2008;Markowski and Richardson 2014). Reliable thermodynamic observations above the ground have been conspicuously missing.…”
Section: Aboveground Thermodynamic Observations In Convective Storms mentioning
confidence: 99%
“…Remote sensing platforms (e.g., Raman lidars, radiometers), either ground based, airborne, or spaceborne, are not particularly useful owing to the relatively long times required to complete a scan and the inability to penetrate clouds and precipitation. Surface-based observing systems have enabled great strides in our understanding of the importance of the thermodynamic characteristics in tornadogenesis (e.g., Markowski et al 2002;Shabbott and Markowski 2006;Grzych et al 2007;Hirth et al 2008;Markowski et al 2012;Weiss et al 2015), though such groundbased observations can only provide information at the bottom of the trajectories that enter a developing and/or mature tornado-trajectories that spend a considerable time aloft prior to reaching the surfaceand only where there are roads.…”
Section: Aboveground Thermodynamic Observations In Convective Storms mentioning
confidence: 99%
“…Supercell downdrafts are known to be crucial for tornadogenesis, but they are a ubiquitous aspect of supercells and therefore their presence alone tells us little about the prospects for tornadogenesis. There is evidence that relatively warm (though typically still negatively buoyant) downdrafts may contribute to tornadogenesis (Markowski 2002;Markowski et al 2002;Grzych et al 2007). More recently, field observations have shown that localized enhancements of rear-flank outflow and sudden cascades of precipitation from aloft on the rear flank sometimes immediately precede the intensification of near-ground rotation (Lee et al 2012;Kosiba et al 2013;Snyder et al 2013).…”
Section: Introductionmentioning
confidence: 99%